2022
DOI: 10.3389/fmolb.2022.917725
|View full text |Cite
|
Sign up to set email alerts
|

Cryo-EM Structure of an Atypical Proton-Coupled Peptide Transporter: Di- and Tripeptide Permease C

Abstract: Proton-coupled Oligopeptide Transporters (POTs) of the Major Facilitator Superfamily (MFS) mediate the uptake of short di- and tripeptides in all phyla of life. POTs are thought to constitute the most promiscuous class of MFS transporters, with the potential to transport more than 8400 unique substrates. Over the past two decades, transport assays and biophysical studies have shown that various orthologues and paralogues display differences in substrate selectivity. The E. coli genome codes for four different … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 80 publications
0
10
0
Order By: Relevance
“…DtpB adopts the canonical MFS fold, characterized by two six transmembrane helix bundles. The N-and C-terminal bundles are linked by the HA-HB helices, as observed in other bacterial POTs [3][4][5][6][7][8]10,18,[32][33][34][35]37,39 . The overall structure of DtpB is similar to DtpA, DtpC, and DtpD with Cα atom RMSD (root-mean-square deviation) values of 0.9, 1.3, and 1.2 Å, respectively.…”
Section: Dtpb Crystallized In An Inward Facing Open (If Open) State I...mentioning
confidence: 64%
See 4 more Smart Citations
“…DtpB adopts the canonical MFS fold, characterized by two six transmembrane helix bundles. The N-and C-terminal bundles are linked by the HA-HB helices, as observed in other bacterial POTs [3][4][5][6][7][8]10,18,[32][33][34][35]37,39 . The overall structure of DtpB is similar to DtpA, DtpC, and DtpD with Cα atom RMSD (root-mean-square deviation) values of 0.9, 1.3, and 1.2 Å, respectively.…”
Section: Dtpb Crystallized In An Inward Facing Open (If Open) State I...mentioning
confidence: 64%
“…Transport inhibition experiments indicated that the binding sites of DtpA and DtpB interact with a large number of substrates and peptidomimetic drugs in a similar fashion as the extensively studied mammalian homolog PepT1 16,[19][20][21][22][23][24] . DtpC and DtpD, however, were classified as atypical POTs, as they were shown previously to favour positively charged peptides as substrates 18,22,[25][26][27][28][29][30] .…”
Section: Introductionmentioning
confidence: 85%
See 3 more Smart Citations